2015
DOI: 10.1158/2326-6066.cir-14-0216
|View full text |Cite
|
Sign up to set email alerts
|

Virotherapy with a Semliki Forest Virus–Based Vector Encoding IL12 Synergizes with PD-1/PD-L1 Blockade

Abstract: Virotherapy and checkpoint inhibitors can be combined for the treatment of cancer with complementarity and potential for synergistic effects. We have developed a cytolytic but nonreplicative viral vector system based on Semliki Forest virus that encodes IL12 (SFV-IL12). Following direct intratumoral injection, infected cells release transgenic IL12, die, and elicit an inflammatory response triggered by both abundantly copied viral RNA and IL12. In difficult-to-treat mouse cancer models, such as those derived f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 25 publications
3
80
0
Order By: Relevance
“…1A), known to be of difficult treatment by immunotherapy (32,33). In this case, mice bearing tumors for 11 days showed a radiotherapy-dependent control of contralateral tumors, when distant radiotherapy was combined with either anti-PD1 or anti-CD137 mAb.…”
Section: Resultsmentioning
confidence: 98%
“…1A), known to be of difficult treatment by immunotherapy (32,33). In this case, mice bearing tumors for 11 days showed a radiotherapy-dependent control of contralateral tumors, when distant radiotherapy was combined with either anti-PD1 or anti-CD137 mAb.…”
Section: Resultsmentioning
confidence: 98%
“…Investigators have been exploring combination strategies in order to enhance the overall efficacy of these novel treatment strategies while limiting the toxicity. Indeed, a number of studies have explored the combination of an OV with checkpoint blockade in cancer models3435363738, and ongoing clinical trials are addressing this. These studies have demonstrated that viral infection overcomes tumour resistance to immune checkpoint blockade immunotherapy3639.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, despite these results, IL12 remains as a recognized anticancer agent with a great potential for synergistic combinations with other immunotherapies and/or conventional cancer treatments. 37,38 Finally, there is increasing evidence showing the importance of host responses to viral vectors for successful experimental cancer therapies. There is evidence of IL12 and IFN interplay in the control of tumor growth.…”
Section: Discussionmentioning
confidence: 99%